Pengaruh social media marketing dan Brand equity terhadap minat beli heylocal.id - Tasya Eka Putri; Hendri Dunan (Jurnal Widya, 2022)
The purpose of the consequences of this examine is to decide the impact of social media advertising and logo cost at the shopping for hobby of heylocal.id. This form of studies is subject studies and library studies. This research method is a descriptive research layout. The research variables include impartial variables (independent), specifically social media advertising (X1) and brand fairness (X2), while the structured variable (structured) is shopping for interest (Y). The populace on this examine are Heylocal.id clients who've bought heylocal.id merchandise. The sampling approach utilized by the writer is non-chance sampling. The non-probability sampling approach used in sampling in this study is a directed sampling method. The types and sources of records received via the authors are primary information received at once from the studies item via using facts series tools immediately associated with the subject because the source of the information sought, and secondary information acquired from other parties and not immediately from researchers the object of studies. In this study, the researchers used the method from the field and the literature. The data collection approach used in this examine became observation and questionnaire techniques. The analysis method used is quantitative evaluation. The outcomes of this take a look at show that social media advertising has a fine and tremendous impact on product buy hobby on Heylocal.id, established and suitabel. Emblem fairness has a positive and significant impact on product buy hobby on Heylocal.id, established and ideal. Social media advertising and marketing and brand equity combined have a superb and sizable effect on product buy interest on Heylocal.id, validated and proper.